Time series investigation of electrical resistivity tomography reveals the key drivers of tide and storm on groundwater discharge. (5th March 2023) - Xing, Cheng; Zhang, Yufeng; Guo, Xiujun; Sun, Jitong
Abstract: Storms, as a natural dynamic force, not only couple with the tide but also enhance wave action in the coastal zone. However, their impact on the seawater-groundwater exchange process of coastal aquifers remains poorly understood. In this study, the sandy tidal flat of Shilaoren, Qingdao, was selected as the study area. Electrical resistivity tomography (ERT) and hydrological monitoring were used to investigate the seawater-groundwater interactions due to storms. The results showed that the interface between saline and fresh groundwater, identified by multiple upper saline plumes (USPs) and freshwater discharge tubes (FDTs), occurs during the entire tidal cycle. During the storm, FDT was first infilled with seawater, then separated from the beach surface until the ebbing tide; eventually, it occurred again in the lower intertidal zone. After the storm, the saline groundwater that invaded during the storm began to discharge rapidly, and multiple USPs and FDTs were formed during the ebbing tide. In addition, under the same tide level, the groundwater outflow rate and discharge flux during the storm were 0.82 and 0.75 times lower than those after the storm, respectively. This work improves the understanding of seawater-groundwater interactions during storms and reveals the key influencing factors, providing a field observation and theoretical basis for quantifying SGD-derived solute flux and further mechanistic studies. Highlights: ERT is an effective method for real-time monitoring of salinity changes in coastal aquifer. The distribution characteristics and changes of USP and FDT during and after the storm are described. The groundwater outflow rate and discharge flux during the storm were 0.82 and 0.75 times lower than those after the storm.